Minimally important difference in diffuse systemic sclerosis: results from the d-penicillamine study. Issue 10 (15th March 2006) - Khanna, D; Furst, D E; Hays, R D; Park, G S; Wong, W K; Seibold, J R; Mayes, M D; White, B; Wigley, F F; Weisman, M; Barr, W; Moreland, L; et al.
Abstract : Objective: To estimate minimally important differences (MIDs) in scores for the modified Rodnan Skin Score (mRSS) and Health Assessment Questionnaire—Disability Index (HAQ-DI) in a clinical trial on diffuse systemic sclerosis (SSc). Participants and methods: 134 people participated in a 2-year, double-blind, randomised clinical trial comparing efficacy of low-dose and high-dose d -penicillamine in diffuse SSc. At 6, 12, 18 and 24 months, the investigator was asked to rate the change in the patient's health since entering the study: markedly worsened, moderately worsened, slightly worsened, unchanged, slightly improved, moderately improved or markedly improved. Patients who were rated as slightly improved were defined as the minimally changed subgroup and compared with patients rated as moderately or markedly improved. Results: The MID estimates for the mRSS improvement ranged from 3.2 to 5.3 (0.40–0.66 effect size) and for the HAQ-DI from 0.10 to 0.14 (0.15–0.21 effect size). Patients who were rated to improve more than slightly were found to improve by 6.9–14.2 (0.86–1.77 effect size) on the mRSS and 0.21–0.55 (0.32–0.83 effect size) on the HAQ-DI score. Conclusion: MID estimates are provided for improvement in the mRSS and HAQ-DI scores, which can help in interpreting clinical trials on patients with SSc and be used for sample size calculation for future clinical trials on diffuse SSc.